2012
DOI: 10.1007/s10156-011-0315-1
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Nocardia farcinica infection in a patient with myasthenia gravis successfully treated by linezolid: a case report and literature review

Abstract: Nocardiosis is increasingly being diagnosed because of a growing population of immunocompromised hosts and improvements in the detection of Nocardia species in clinical laboratories. Historically, sulphonamides have been the first-line therapy for the treatment of nocardiosis, but sulphonamides tend to have a high rate of drug allergy in clinical settings. In this report, we described a disseminated Nocardia farcinica infection that occurred in a patient with myasthenia gravis who suffered from multiple drug a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…However, a treatment failure has been described in three patients treated with minocycline for pulmonary nocardiosis, with the patients developing brain abscesses under treatment. Susceptibility testing was not available in two cases, but the strain was susceptible in vitro in the third patient (15,25). The use of minocycline as a second-line oral drug for CNS nocardiosis should be limited to patients with a susceptible isolate (MIC Ͻ 0.5 g/ml) and requires a close follow-up of efficacy.…”
Section: Case Reportmentioning
confidence: 99%
“…However, a treatment failure has been described in three patients treated with minocycline for pulmonary nocardiosis, with the patients developing brain abscesses under treatment. Susceptibility testing was not available in two cases, but the strain was susceptible in vitro in the third patient (15,25). The use of minocycline as a second-line oral drug for CNS nocardiosis should be limited to patients with a susceptible isolate (MIC Ͻ 0.5 g/ml) and requires a close follow-up of efficacy.…”
Section: Case Reportmentioning
confidence: 99%
“…Increase in the infections caused by these organisms, with different clinical forms of systemic and disseminated forms of nocardiosis in transplant recipients, tuberculosis, liver cirrhosis, cancer, diabetes, AIDS and patients under treatment with immunosuppressive drugs and broad spectrum antibiotics in the world, reveals more importance of isolation and identification of these agents [2,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Various studies have shown that identification and isolation of these agents in soil of different areas help to diagnose nocardiosis [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Resistance patterns also depend on the exact species of Nocardia, which emphasizes the paramount importance of an accurate microbiological diagnosis. Recently, there have been favourable case reports of linezolid as an effective agent against nocardiosis [11]. Unfortunately, the duration of treatment with linezolid is limited due to the polyneuropathy it can cause.…”
Section: Discussionmentioning
confidence: 99%